PENDIDIKAN ISLAM DI PULAU BAWEAN: SEJARAH DAN PEMBENTUKANNYA - Abdul Wahid (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
Islamic Education in Bawean Island Indonesia began since the arrival of Islam to the island during 16th century. Initially, Islamic education activities were carried out at places such as houses, musolla and mosques. At this early stage, Islamic education was yet a formal institution and was conducted individually. From its historical journey, Islamic education at Bawean Island has progressed to become a formal institution in the form of madrasah which united Islamic education with Indonesian national education. This study aims to look at the early history of Islamic education at Bawean Island and afterwards at the resulting development process. Results have shown that students’ achievement at Islamic education institution was excellent and the response from the society was encouraging. To conclude, Islamic education institution at Bawean Island was still preferred and capable of competing with the general education.